Assessment of Intellectual and Visuo- Spatial Abilities in Children and Adults with Williams Syndrome (2012)
The Williams-Beuren syndrome (SWB), also known as Williams syndrome, is a contiguous gene deletion of the region 7q.11.23. The main clinical characteristics are typical faces, supravalvular aortic stenosis, failure to thrive, short stature, transient neonatal hypercalcemia, delayed language, friendly personality, hyperacusis and intellectual disability. The diagnosis of SWB is confirmed by the detection of micro deletion by different techniques of molecular cytogenetics, FISH, MLPA or polymorphic markers. This study assessed the verbal intelligence quotient (IQ) and performance and visuospatial skills in children and adults with WBS. The composed group was of 31 WBS patients (19 M and 12 F), whose ages ranged from 9 to 26 years (M 14.45 y). All patients had the diagnosis confirmed molecularly. The tests used were the WISC-III, WAIS-III and Rey-Osterrieth Complex Figure Test. The results indicated a total IQ ranged from 51 to 86 (M 63): 22 with mild intellectual disability, 4 with moderate intellectual disability, 4 borderlines and 1 below the normal media. All patients had marked visual-spatial deficits. The results suggest nonverbal reasoning, visuo-spatial perception, spatial representation, working memory, motor planning and executive functions are very affected in this group.